2010
DOI: 10.4103/1596-3519.68352
|View full text |Cite
|
Sign up to set email alerts
|

Malaria among antenatal clients attending primary health care facilities in Kano state, Nigeria

Abstract: Malarial infection is common among the ANC clients attending PHC facilities in Kano state and the infection is commonly associated with anemia. Intermittent Preventive Treatment (IPT) should be provided especially among primigravid, secondigravid and younger mothers at PHC centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
38
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 22 publications
13
38
5
Order By: Relevance
“…We observed a significant negative correlation between plasmodial infection and CD4 lymphocyte count among Plasmodium malariainfected subjects, with r = -0.56 (p = .001). Table 1 shows the mean values of CD4, parasite load, and age of subjects , and 39.2% in Kano to 60% in Lagos 10 . Similarly, another study 11 among Antenatal clients (ANCs) from a peri-urban community in Lagos reported a 44.2% prevalence of asymptomatic malaria at booking among primgravidae attending a Primary Health Care (PHC) facility, which was significantly lower than 33.6% prevalence found among multigravidae 12 .…”
Section: Resultsmentioning
confidence: 99%
“…We observed a significant negative correlation between plasmodial infection and CD4 lymphocyte count among Plasmodium malariainfected subjects, with r = -0.56 (p = .001). Table 1 shows the mean values of CD4, parasite load, and age of subjects , and 39.2% in Kano to 60% in Lagos 10 . Similarly, another study 11 among Antenatal clients (ANCs) from a peri-urban community in Lagos reported a 44.2% prevalence of asymptomatic malaria at booking among primgravidae attending a Primary Health Care (PHC) facility, which was significantly lower than 33.6% prevalence found among multigravidae 12 .…”
Section: Resultsmentioning
confidence: 99%
“…6,7,11,12 The prevalence rates found are quite variable, given the endemic nature of the disease and the preventive measures put in place to fight the infection. The highest prevalence rates were found in Nigeria with figures as high as 60%.…”
Section: Discussionmentioning
confidence: 99%
“…10 The absence of clinical signs does not imply absence of disease since literature describes asymptomatic disease. 4,6,11,12 The clinical presentation of PF infection varies greatly from one pregnant woman to another, with some patients having fever and chills, to others being totally asymptomatic. 13 Fever remains the most dreaded symptom of malaria in pregnancy and as such, most fevers in pregnancy are considered related to malaria until proven otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Up to 16-95.4% of asymptomatic parasitemia in pregnancy had been reported in various studies with associated maternal anemia and low birth weight. [6][7][8][9][10][11][12][13] This study was aimed at determining the prevalence of asymptomatic malaria parasitemia among unbooked clients presenting in labor in the Federal Teaching Hospital Abakaliki. This will help to detect those who have the problem and appropriate treatment administered in the short run and to show the enormity of the problem to help create awareness and to scale up preventive measures against this public health problem in the long run.…”
Section: Introductionmentioning
confidence: 99%